Development of new peak-height models for a continuous method of mixture interpretation. (December 2015) - Manabe, Sho; Hamano, Yuya; Kawai, Chihiro; Morimoto, Chie; Tamaki, Keiji
Abstract: DNA mixture interpretation based on a continuous model is an effective strategy for calculating rigorous likelihood ratios using peak heights and considering stochastic effects. Such a model would require the elucidation of various biological parameters affecting the expected peak heights. In the present study, we estimated the distributions of locus-specific amplification efficiency, heterozygote balance, and stutter ratio in 15 commercially available short tandem repeat (STR) loci using 234 single-source DNA samples. Our data suggested that the locus-specific amplification efficiency followed a normal distribution, whereas the heterozygote balance followed a log-normal distribution for each locus. We modeled log-normal distributions for stutter ratios with allele-specific mean values, which exhibited a positive correlation with allele repeat numbers. However, with the D8S1179, D21S11, and D2S1338 loci, the log-normal distribution did not fit our data because of the complex repeat structures involved. Therefore, an alternative model for each of these three loci will need to be incorporated into a software program based on a continuous model.